The Expression of Inflammasomes NLRP1 and NLRP3, Toll-Like Receptors, and Vitamin D Receptor in Synovial Fibroblasts From Patients With Different Types of Knee Arthritis - Sakalyte, Regina; Denkovskij, Jaroslav; Bernotiene, Eiva; Stropuviene, Sigita; Mikulenaite, Silvija Ona; Kvederas, Giedrius; Porvaneckas, Narunas; Tutkus, Vytautas; Venalis, Algirdas; Butrimiene, Irena (Frontiers in Immunology, 2022)
Activated rheumatoid arthritis (RA) synovial fibroblasts (SFs) are among the most important cells promoting RA pathogenesis. They are considered active contributors to the initiation, progression, and perpetuation of the disease, therefore early detection of RASF activation could advance contemporary diagnosis and adequate treatment of undifferentiated early inflammatory arthritis (EA). In this study, we investigated the expression of nucleotide-binding, oligomerization domain (NOD)-like receptor family, pyrin domain containing (NLRP)1, NLRP3 inflammasomes, Toll-like receptor (TLR)1, TLR2, TLR4, vitamin D receptor (VDR) and secretion of matrix metalloproteinases (MMPs) in SFs isolated from patients with RA, osteoarthritis (OA), EA and control individuals (CN) after knee surgical intervention. C reactive protein, general blood test, anti-cyclic citrullinated peptide (anti-CCP), rheumatoid factor (RF), vitamin D (vitD) in patients sera were performed. Cells were stimulated or not with 100 ng/ml TNFα or/and 1 nM or/and 0.01 nM vitamin D3 for 72h. The expression levels of NLRP1, NLRP3, TLR1, TLR2, TLR4 and VDR in all examined SFs was analysed by RT-qPCR. Additionally, the secretion of IL-1β by SFs and MMPs were determined by ELISA and Luminex technology. The expression of NLRP3 was correlated with the levels of CRP, RF and anti-CCP, suggesting its implication in SF inflammatory activation. In the TNFα-stimulated SFs, significantly lower expression of NLRP3 and TLR4 was observed in the RA group, as compared to the other tested forms of arthritis. Moreover, upregulation of NLRP3 expression by TNFα alone or in combination with vitD3 was observed, further indicating involvement of NLRP3 in the inflammatory responses of SFs. Secretion of IL-1β was not detected in neither sample, while TNF-α upregulated the levels of secreted MMP-1, MMP-7, MMP-8, MMP-12 and MMP-13 in all patient groups. Attenuating effects of vitD on the expression of NLRP3, TLR1 and TLR4 suggest potential protective effects of vitD on the inflammatory responses in SFs. However, longer studies may be needed to confirm or fully rule out the potential implication of vitD in SF activation in inflammatory arthritis. Both VDR and NLRP3 in the TNFα stimulated SFs negatively correlated with the age of patients, suggesting potential age related changes in the local inflammatory responses.